Evolution and dynamics of online paid knowledge in China: a comprehensive review from 2016 onwards - Bin, Liu; Imran Yasin, Megat Al; Abdul Rahman, Saiful Nujaimi (Human Resource Management Academic Research Society, 2023)
Online Paid Knowledge, in which users pay for online access to information and services pertaining to knowledge, has become a prominent phenomenon in the digital age. This article provides an analysis of the scholarly literature on Online Paid Knowledge in China from 2016 forward. This study outlines four significant phases of Online Paid Knowledge research in China. It examines the conception and evolution of Online Paid Knowledge, as well as the economic models and legal mechanisms of the OPK platform and the factors that influence user payment behavior. The review aims to identify the phases, trends, and focal points of academic research in this field. It contributes to a greater comprehension of the evolution and dynamics of Online Paid Knowledge in China, revealing its influence on content companies and academic research.